Ginger Pye - Estes, Eleanor, 1906-1988. (Boston : Houghton Mifflin Harcourt, 2017)
The disappearance of a new puppy named Ginger and the appearance of a mysterious man in a mustard yellow hat bring excitement into the lives of the Pye children.
Originlly published in 1951.
"Winner of the Newberry Medal"--Page [4] of cover.
Keywords: Dogs -- Fiction; Brothers and sisters -- Fiction